Hydrogen Environmental Benefits Depend on the Way of Production: An Overview of the Main Processes Production and Challenges by 2050. Issue 10 (6th October 2021) - Germscheidt, Rafael L.; Moreira, Daniel E. B.; Yoshimura, Rafael G.; Gasbarro, Nathália P.; Datti, Evandro; dos Santos, Pãmyla L.; Bonacin, Juliano A.
Abstract : Dye‐Sensitized Solar Cells In article number 2100093 by Anish Babu Athanas and Swarnalatha KalaiyarHerein, a new coumarin‐based ruthenium(II) dye with tunable photophysical and redox properties is designed and synthesized. The dyesensitized TiO2 photoelectrodes are tested as photocurrent generators for both water‐splitting reactions and dye‐sensitized solar cells. The photoelectrochemical devices furnish a water‐splitting efficiency of 4.98% and power conversion efficiency of 4.16%.